Individual Heterogeneity, Job Matching, and Returns to Tenure in Germany - Kenneth A. Couch (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
Data from the German Socio-Economic Panel are used to examine the roles of individual heterogeneity and job match quality in generating commonly observed wage-tenure profiles. The evidence presented in the paper indicates that once those factors are reflected in the estimations, the returns to seniority are no longer measurable. Job match quality appears to be the dominant factor in the German labor market in generating an upward sloping wage-tenure profile.
Keywords: 330; Arbeitsmobilität; Betriebszugehörigkeit; Personalauswahl; Vergütungssystem; Lohn; Deutschland